2021
DOI: 10.3390/chemosensors9020035
|View full text |Cite
|
Sign up to set email alerts
|

Graphite Studded with Facile-Synthesized Cu2O Nanoparticle-Based Cubes as a Novel Electrochemical Sensor for Highly Sensitive Voltametric Determination of Mebeverine Hydrochloride

Abstract: Herein, a feasible chemical reduction method followed by intensive mixing was applied for the preparation of an attractive material based on graphite studded with cuprous oxide nanoparticle-based cubes (Cu2ONPs–C@G). Transmission electron microscope (TEM), scanning electron microscope (SEM), X-ray diffraction (XRD) and cyclic voltammetry (CV) were utilized for characterization. Cuprous oxide nanoparticles (Cu2ONPs), with a diameter range mainly distributed from 4 to 20 nm, aggregate to form microcubes (Cu2ONPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…1 A comprehensive study of the literature revealed the dominance of analytical methods for MBV, including spectrophotometric, 2-11 HPLC, [12][13][14][15][16][17][18] uorometric, 19,20 and electrochemical methods. [21][22][23][24][25][26][27] Although these methods provided a high level of specicity, they are unable to apply rapid in situ detection of MBV. Moreover, these previously described methods still had several limitations, such as the need to use a lot of expensive, hazardous organic reagents that would hurt the environment.…”
Section: Introductionmentioning
confidence: 99%
“…1 A comprehensive study of the literature revealed the dominance of analytical methods for MBV, including spectrophotometric, 2-11 HPLC, [12][13][14][15][16][17][18] uorometric, 19,20 and electrochemical methods. [21][22][23][24][25][26][27] Although these methods provided a high level of specicity, they are unable to apply rapid in situ detection of MBV. Moreover, these previously described methods still had several limitations, such as the need to use a lot of expensive, hazardous organic reagents that would hurt the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these combined unit methods involve high costs and time for analysis [4][5][6]. Analytical methods such as spectrophotometry [7], mass-spectrometry [8], chromatography [9] and electrophoresis [10], electrochemistry [11] and their joint devices have been used for analytical purposes. Because of the disadvantages of the mentioned separation techniques or combination analyzers, analytical chemists opt to use spectroscopic methods (rather than separation techniques) to enable rapid analysis at low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these combined unit methods involve high costs and time for analysis [4][5][6]. Analytical methods such as spectrophotometry [7], massspectrometry [8], chromatography [9] and electrophoresis [10], electrochemistry [11] and their joint devices have been used for analytical purposes. Herewith the disadvantages of the mentioned separation techniques or combination analyzers, analytical chemists opt to use spectroscopic methods (rather than separation techniques) to enable rapid analysis at low cost.…”
Section: Introductionmentioning
confidence: 99%